Pathologic N1 disease in lung cancer: the segmental and subsegmental lymph nodes - Riquet, Marc; Pricopi, Ciprian; Mangiameli, Giuseppe; Arame, Alex; Badia, Alain; Le Pimpec Barthes, Françoise (Journal of Thoracic Disease; Vol 9, No 11 (November 29, 2017): Journal of Thoracic Disease (Quantitative Imaging of Thoracic Diseases), 2017)
N1 disease represents a heterogeneous group of non-small cell lung carcinoma (NSCLC). Pathologic N1 disease may involve one or more lymph node (LN) in the lung classified by Mountain and Dressler (1) in five stations corresponding to their anatomical locations: the hilar LNs, the Interlobar LNs, the lobar LNs, the segmental LNs and the subsegmental LNs being termed station 10, 11, 12, 13 and 14, respectively. In the seventh edition of the TNM classification for lung cancer (2), N1 disease was classified in two zones, hilar/interlobar zone regrouping stations 10 and 11 and peripheral zone regrouping stations 12, 13 and 14.